SINERGITAS PEMANGKU KEPENTINGAN DALAM KERANGKA PENGEMBANGAN EKONOMI KREATIF DI KAWASAN KASULTANAN BANTEN KOTA SERANG - Yedi Rusyadi; Ipah Ema Jumiati; Rina Yulianti (Jurnal Kebijakan Pembangunan Daerah, 2022)
The lack of creative centers, the low quality of creative human resources, unsupportive regulations, weak access to capital and weak marketing distribution methods are obstacles to the development of the creative economy. The purpose of this study was to analyze the synergy of stakeholders through the principle of effective coordination which was built in an effort to develop the creative economy in the Banten Sultanate Region, Serang City. Coordination between different stakeholder functions is important in building synergy. Therefore, the synergy of stakeholders can be reviewed through several principles of effective coordination, including coordination through direct contact, coordination in the early stages, coordination as a reciprocal relationship and coordination as a continuous process. The study used descriptive methods through a qualitative approach by analyzing the results of interviews and secondary data obtained from the results of the literature study. The results of the study indicate that stakeholders cannot carry out an effective coordinating role. This condition reflects that the synergy built between stakeholders in the framework of developing the creative economy in the Banten Sultanate Area, Serang City has not run optimally.